DINAMIKA MASYARAKAT PERBATASAN (Eksistensi Perantau Bugis di Pulau Sebatik Kalimantan Utara: Perspektif Cultural Studies)(THE DYNAMICS OF BORDER SOCIETY (The Existence of Bugis Migrants in Sebatik Island North Kalimantan: Perspective of Cultural Studies)) - Saleh, Muhammad Hairul (Pusjar SKPP Lembaga Administrasi Negara, 2015)
This article basically aim to give a description about the existence of Bugis migrants on the Sebatik island by focusing on the ability of Bugis migrants in creating and managing the economic resources linked with the talent to build relationships, both economically and socially as an effort to participate in the development of Sebatik Island. The research method used is descriptive qualitative, in which data and related information are collected through literature study and empirical research that are concerned about the border's issues, particularly the border of Indonesia and Malaysia. Another technique used is depth interviews with the Bugis migrants. These studies suggest that Bugis migrants in Sebatik Islandare immigrants who have a dream to improve their living standards. With the principle of